Go4Hybrid: Grey Area Mitigation for Hybrid RANS-LES Methods Results of the 7th Framework Research Project Go4Hybrid, Funded by the European Union, 2013-2015 - Mockett, Charles; Haase, Werner; Schwamborn, Dieter; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2018)
This book reports on the EU-funded 7th Framework project, Go4Hybrid (Grey Area Mitigation for Hybrid RANS-LES Methods). It presents new findings concerning the accuracy and reliability of current hybrid RANS-LES methods. It describes improved formulations of both non-zonal and embedded hybrid strategies, together with their validation in a broad range of flow cases, and highlighting some key industrial applications. The book provides students, researchers and professionals in the field of applied computational fluid dynamics with a timely, practice-oriented reference guide.    .
Keywords: Fluid mechanics; Continuum mechanics; Dynamics; Nonlinear theories; Engineering Fluid Dynamics; Continuum Mechanics; Applied Dynamical Systems